Preventive Effect of Ophthalmic Lenses on Cataract, is it Real? - Nascimento, Henrique; Roque, Ana da Costa (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Knowing that the prevalence of crystalline cataracts  after 40 years is relatively high and that exposure to UV rays is a factor for its appearance, since the lens is an absorber of these rays, it was intended with this pilot study to verify the relationship between the appearance of crystalline nuclear sclerosis and the time that patients take from the use of ophthalmic lenses, since they absorb most of these rays under normal conditions of use.